2020
DOI: 10.3390/w12020414
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analyses of Meteorological Variables and Lake Levels for Two Shallow Lakes in Central Turkey

Abstract: Trend analyses of meteorological variables play an important role in assessing the long-term changes in water levels for sustainable management of shallow lakes that are extremely vulnerable to climatic variations. Lake Mogan and Lake Eymir are shallow lakes offering aesthetic, recreational, and ecological resources. Trend analyses of monthly water levels and meteorological variables affecting lake levels were done by the Mann-Kendall (MK), Modified Mann-Kendall (MMK), Sen Trend (ST), and Linear trend (LT) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 31 publications
(45 reference statements)
0
15
0
3
Order By: Relevance
“…The application of the trend test to analyze the impact of climate change on runoff is a common practice implemented by many researchers [89][90][91]. In this study, the result of the modified MK test indicated that the trend of annual temperature and annual potential evapotranspiration significantly increased, while precipitation showed an insignificant decreasing trend in the upstream and downstream regions of the KRB.…”
Section: Discussionmentioning
confidence: 71%
“…The application of the trend test to analyze the impact of climate change on runoff is a common practice implemented by many researchers [89][90][91]. In this study, the result of the modified MK test indicated that the trend of annual temperature and annual potential evapotranspiration significantly increased, while precipitation showed an insignificant decreasing trend in the upstream and downstream regions of the KRB.…”
Section: Discussionmentioning
confidence: 71%
“…Ardından, xi veri sütunu başlangıç olarak kullanılır ve diğer sıralanmış xj ile Denklem 2'deki signum fonksiyonu kullanılarak Denklem 3'teki "S" değeri hesaplanır. Bu işlemler sonucunda tüm veri çiftlerinin farkı (xj−xi) ile pozitif ve negatif değerlerin sayısının toplamı bulunmuş olur (Demir & Keskin, 2020;Yagbasan, Demir, & Yazicigil, 2020).…”
Section: Mann-kendall (Mk)unclassified
“…If (tcal) account value exceeds the accepted range, there is a trend and it is increasing or decreasing according to the sign. If it does not exceed (-tcritical <tcal <tcritical), it is said that there is no trend (V. Demir, 2018;Yagbasan et al, 2020).…”
Section: Linear Trend (Lt)mentioning
confidence: 99%